Peran Bu Nyai dalam Pengembangan Ekonomi Pesantren di Sumatera Selatan - Rohmaniyah, Naila; Panorama, Maya; Syaifulloh, Ahmad; Santoso, Fattah Setiawan (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The economic development of pesantren is one of the trends in the current era. This study aims to determinine the role of Bu Nyai in the economic development of pesantren in South Sumatra. Researchers examined psantren that have businesses in the fashion sector. By using qualitative research methods, researchers obtained the following results: 1) Bu Nyai as business leader is responsible for strategic management and fashion business operations. 2) The fashion bisiness can meet the needs of pesantren and school uniform, and contribute to improving the overall infrastructure and facilities. 3) Bu Nyai`s role has a positive impact on the economic development of pesantren, namely improving the welfare of student by empowering students through pesantren business.